(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
To optimize the performance of the Satpol PP it is necessary to build Satpol PP Institutions that are able to support the realization of peaceful, orderly and orderly regional conditions. The institutional arrangement of the Satpol PP does not only consider the criteria for population density in an area, but also the burden of duties and responsibilities carried out as well as the risk of the safety of the civil servise police. For this reason, the importance of the duties and functions of the daily freelancers at the Satpol PP in security and law enforment in the coming times will be even more severe, as seen from their ability to work and motivation in their work and arrogant attitudes of daily workers Satpol PP which has work disicipline which according to the community is often shown when carrying out its role. The purpose of this study was to find out and analyze the influence of work ability, work motivation, and work disicipline on the performance of freelance daily workers in the manado city Satpol PP Office. The type of research used is a survey research method with a quantitative sampling so that the data used are primary data through questionnaires with a sample of 82 daily freelancers processed with a likert scale. The analytical tool used in this study uses SPSS21. For the results of the study at a significant lefel of 0,01% which indicaties that the results of the F test indicate there is a positive effect of work ability, work motivation, and work disicipline simultaneously on the performance of casual daily workers. For the t-test that has been known from the results of the analysis that the work ability has a positive and significant effect on the performance of freelance daily workers in the Manado City Satpol PP Office. Based on the results of research that has been known and analyzed, it can be concluded that work ability has a positive and significant effect while work motivation and work discipline have apositive and not significant coefficient of determination of work ability, work motivation and work disicipline in explaning variable variantions in daily freelance performance are very limited. For this reason, advice has been given to the existing institutions in the Regional Office of the Satpol PP in Manado so that they must pay attention to their work ability, work motivation, and discipline by encouraging or encouraging work by providing work, work colleagues pleasant working conditions in order to improve the performance of freelance daily workers in the Manado City Satpol PP Office. Keyword : Ability, Motivation, Discipline